IMPLEMENTASI E-GOVERNMENT DALAM PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BONE - Lestari, Resti; Madani, Muhlis; Malik, Ihyani (Universitas Muhammadiyah Makassar, 2023)
This study aimed to find out how the implementation of e-government in public services at the Department of Population and Civil Registry of Bone Regency. This study used qualitative with descriptive research type. The data collection techniques used observation, interviews, and documentation. The results of this study indicated that the implementation of e-Government in public services at the district population and civil registry offices provided good benefits. It could be seen from the support element, namely the Population and Civil Registry Office of Bone Regency had implemented this online-based service (e-Government) to improve and produce excellent or good service. Elements of capacity consisted of: 1) competent human resources who became operators, 2) financial sources of funds, 3) adequating infrastructure resources for services. The value element of the benefits felt by the Population and Civil Registry Office of Bone Regency as a service provider, such as the lack of queues and the community perceived as service recipients, such as the time spent in the service becomes effective and efficient.